Microbial abundance and diversity in water, and immune parameters of red tilapia reared in bioflocs system with different fish density (25 fish/m3, 50 fish/m3, and 100 fish/m3) - Agustinus, Frid; Widanarni, .; Ekasari, Julie (Indonesian Society of Scientific Aquaculture (ISSA), 2010)
ABSTRACTThe objective of this experiment was to study microbial abundance and diversity in the water, and immune parameters of red tilapia Oreochromis sp. cultured in bioflok system with different fish stocking densities. The experiment comprised of two different factors, carbon source addition (bioflocs and control), and fish stocking density (25 fish/m3, 50 fish/m3, dan 100 fish/m3), with an experimental period of 99 days. Microbial load in water was determined biweekly, whereas immune parameters represented by fish blood profile were measured on day 0, 50, and 90. There was no significant difference in total bacteria count in the water of all treatments; there was however a tendency shown by all treatments that the microbial load in water increased along with the culture period. There were 4 genera of bacteria which particularly found in bioflok system, which are Acinetobacter sp., Corynobacterium sp., Listeria sp., dan Pseudomonas sp, and are suggested to play a role in bioflok formation. The percentage of phagocytic index of fish in bioflok system was higher than that in control, and may indicate that bioflok may stimulate the fish immune system.Keywords: bioflocs, red tilapia, bacteria, blood profile. ABSTRAKPenelitian ini bertujuan untuk mengidentifikasi kelimpahan dan keragaman jenis bakteri dalam air dan parameter imunitas ikan nila Oreochromis sp. yang dipelihara dalam sistem bioflok dengan kepadatan ikan yang berbeda. Penelitian terdiri atas dua faktor perlakuan yaitu penambahan sumber carbon (bioflok dan kontrol), dan padat penebaran ikan (25 ekor/m3, 50 ekor/m3, dan 100 ekor/m3) dengan lama waktu pemeliharaan ikan selama 99 hari. Kelimpahan bakteri diukur setiap 2 minggu sekali selama masa pemeliharaan. Parameter imunitas meliputi gambaran darah diukur dengan pengambilan contoh darah yang dilakukan pada tiga ekor ikan pada hari ke 0, 50, dan 99. Kelimpahan bakteri pada semua perlakuan pada setiap titik pengamatan tidak menunjukkan perbedaan yang nyata. Semua perlakuan menunjukkan kecenderungan peningkatan kelimpahan bakteri seiring dengan masa pemeliharaan. Terdapat 4 genus bakteri yang hanya ditemukan pada kolam bioflok yaitu Acinetobacter sp., Corynobacterium sp., Listeria sp., dan Pseudomonas sp yang diduga berperan dalam pembentukan bioflok. Persentase indeks fagositik pada ikan dengan perlakuan bioflok lebih tinggi dibanding kontrol, yang mengindikasikan peran bioflok sebagai stimulus sistem imun.Kata kunci: bioflok, nila merah, bakteri, gambaran darah.